Light ‘Em up: Efficient Screening of Gold Foil Grids in Cryo-EM - Hagen, Wim J. H. (Frontiers in Molecular Biosciences, 2022)
Transmission electron cryo-microscopy (cryo-EM) allows for obtaining 3D structural information by imaging macromolecules embedded in thin layers of amorphous ice. To obtain high-resolution structural information, samples need to be thin to minimize inelastic scattering which blurs images. During data collection sessions, time spent on finding areas on the cryo-EM grid with optimal ice thickness should be minimized as imaging time on high-end Transmission Electron Microscope TEM systems is costly. Recently, grids covered with thin gold films have become popular due to their stability and reduced beam-induced motion of the sample. Gold foil grids have substantially different densities between the gold foil and ice, effectively resulting in the loss of dynamic range between thin and thick regions of ice, making it challenging to find areas with suitable ice thickness efficiently during grid screening and thus increase expensive imaging time. Here, an energy filter-based plasmon imaging is presented as a fast and easy method for grid screening of the gold grids.